Reminiscence of Education in Post-War Years: Sierra Leone as a Case Study - Emerson Abraham Jackson; Hudson Freddie Jackson (Educational Challenges)
The main purposes of this paper are as follows: (I) to provide a historical narrative of Sierra Leone's educational system, (II) to assess the impact of war on the country's educational system and pace of development in the current digital age, and finally, (III) to offer some discourses for policy dialogue in embracing the developmental landscape of the country.